Karakteristik Tinggi Gelombang Laut pada saat Periode Normal, El Niño dan La Niña di Selat Makassar - Sevti Viqa Haiyqal; Aris Ismanto; Elis Indrayanti; Randy Andrianto (Universitas Diponegoro, 2023)
Waves are an important factor in marine science that can have positive and negative impacts on the natural conditions that affect them. Under certain conditions waves can change the coastline, damage marine life, cause tidal flooding, affect coastal buildings and so on. With the energy that waves have, they can affect all human activities such as distribution, utilization of energy sources, utilization of marine biota sources, tourism business, and development of coastal areas. Based on the influence generated, information on wave characteristics is needed based on climate variability that affects local conditions. Climate variability that affects the waters of the Makassar Strait which has a high wave pattern that follows a monsoonal pattern is the El Niño and La Niña phenomena. Using wind data and wave periods for 2013-2022 from Hindcasts-OFS BMKG, this study aims to determine the characteristics of high waves in the Makassar Strait during Normal, El Niño and La Niña phenomena. BMKG-OFS is the third generation data model of wavewatch (WW III) and has a relatively low error value with a range of 0.27 - 0.36 against the observed value of the wave recorder data installed in the Makassar Strait. From the processing it is produced during the Asian Monsoon (December, January, February) and during the Australian monsoon (June, July, August). The characteristics of high waves in the northern and central parts of the Makassar Strait are more influenced by the La Niña phenomenon than El Niño . Characteristics of the wave height in the southern part of the Makassar Strait experienced an increase in wave height both during La Niña and El Niño compared to normal. Gelombang merupakan faktor penting dalam ilmu kelautan yang dapat memberikan dampak positif dan negatif pada kondisi alam yang mempengaruhinya. Pada kondisi tertentu gelombang dapat merubah garis pantai, merusak biota laut, menyebabkan banjir rob, mempengaruhi bangunan pesisir dan lain sebagainya. Dengan energi yang dimilikinya gelombang dapat mempengaruhi segala kegiatan manusia seperti distribusi, pemanfaatan sumber enrgi, pemanfaatan sumber biota laut, bisnis pariwisata, dan pembangunan wilayah pesisir. Berdasarkan pengaruh yang ditimbulkan maka diperlukan informasi karakeristik gelombang berdasarkan varibilitas iklim yang mempengaruhi kondisi lokalnya. Variabilitas Iklim yang mempengaruhi perairan Selat Makassar a yang memiliki pola tinggi gelombang yang mengikuti pola monsunal dalah fenomena El Niño dan La Niña. Dengan menggunakan data angin dan gelombang periode 2013-2022 dari Hindcasts-OFS BMKG, penelitian ini bertujuan untuk mengetahui karakteristik tinggi gelombang di Selat Makassar saat fenomena Normal, El Niño , dan La Niña. BMKG-OFS merupakan data model generasi ketiga dari wavewacth(WW III)dan memiliki nilai error yang reltif rendah dengan rentang sebesar 0,27 - 0,36 terhadap nilai observasi data wave recorder yang terpasang di Selat Makassar. Dari pengolahannya dihasilkan pada saat Monsun Asia (Desember, Januari, Februari) maupun pada saat monsun Australia (Juni, Juli, Agustus). Karakteristik tinggi gelombang di Selat Maksassar bagian utara dan tengah lebih dipengaruhi oleh fenomena La Niña daripada El Niño . Karakteristik tinggi gelombang di Selat Makassar bagian selatan mengalami peningkatan tinggi gelombang baik saat La Niña maupun El Niño terhadap normalnya.